Non-functionalized oil palm waste-derived reduced graphene oxide for methylene blue removal: Isotherm, kinetics, thermodynamics, and mass transfer mechanism - Nur Azrie Hizad Ab Aziz, Nur Azrie Hizad Ab Aziz; Md Ali, Umi Fazara; Ahmad, Anis Atikah; Mohamed Dzahir, Mohd Irfan Hatim; Khamidun, Mohd Hairul; Abdullah, Muhammad Faiq (2023)
The discharge of colored effluents from industries is one of the significant sources of water pollution. Therefore, there is a growing demand for efficient and low-cost treatment methods. An adsorption process with reduced graphene oxide (rGO) synthesized using a novel double carbonization and oxidation method from the natural precursor of oil palm empty fruit bunch (OPEFB) as adsorbent is a promising approach for addressing the problem. In this study, OPEFB biochar was mixed with ferrocene with a ratio of 5:1 (m/m) and oxidized under nitrogen flow at a temperature of 300 C for 20 min, which resulted in 75.8 wt% of yield. The potential of the synthesized rGO as an effective adsorbent for dye removal from water and wastewater was explored using methylene blue (MB) as a model. Several factors were investigated, including adsorbent dosage, initial concentration, contact time, and pH, to obtain the optimum adsorption condition through batch studies. The physical and chemical characteristics of the rGO in terms of functional groups,